Penentuan Agribisnis Unggulan Komoditi Pertanian Berdasarkan Nilai Produksi di Kabupaten Kerinci - Silvia Rahayu (J-MAS (Jurnal Manajemen dan Sains), 2021)
Regional development discusses very strategically in the completion of the implementation of national development. The economic development of each region through economic growth, which is at the same time an indicator, provides an overview of where regional economic development in a given period has resulted in an increase in income for the community which increases per capita income. Agribusiness still has a bigger role in Kerinci Regency, because most of the population of Kerinci Regency supports their lives from the agribusiness sector. The strategic role of agribusiness in the economy of Kerinci Regency includes: food providers for the population of Indonesia, foreign exchange earners through exports, providers of industrial raw materials, increased employment and business opportunities, increased regional income, poverty alleviation and drivers of other economic sectors. In fact, a large number of agribusinesses have considerable production value in Kerinci Regency. This study aimed was to: (1) Analyze the types of superior agricultural commodities, and (2). Review the growth structure of agricultural commodities in Kerinci Regency. The design of this study used descriptive research methods that were descriptions of goals. The aim was that the author wanted to analyze the types of superior agribusiness commodities with the Location Quotient (Location Question) method and examine the structure of the growth of commodity agribusiness in Kerinci Regency. Based on the results of the study, it was found that: the leading agribusiness was the superior agricultural commodity of Kerinci Regency in the period of 2012-2016 based on the calculation of Location Quotient (LQ) Analysis are food crops, horticulture plants and seasonal plantations. Based on Klassen Analysis The typology of the structure of the growth of agricultural commodities is divided into four parts. Advanced and fast developing commodities, in Kerinci Regency are annual and other food crops and horticulture plants. Advanced but depressed commodities consist of annual horticultural crops sub-sector commodities and seasonal plantations. Rapidly developing commodities consist of commodity livestock, forestry and logging sub-sectors. Relatively lagging commodities consist of agricultural services sub-sector and hunting